OP0202 Efficacy and safety of tofacitinib, an oral janus kinase inhibitor, in patients with active psoriatic arthritis and an inadequate response to tumour necrosis factor inhibitors: opal beyond, a randomised, double-blind, placebo-controlled, phase 3 trial. (15th June 2017) - Gladman, DD; Rigby, WFC; Azevedo, VF; Behrens, F; Blanco, R; Kaszuba, A; Kudlacz, E; Wang, C; Menon, S; Hendrikx, T; Kanik, KS
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor under investigation for treatment of PsA. Objectives: Evaluation of efficacy and safety of tofacitinib vs placebo (PBO) in adult patients (pts) with active PsA and an inadequate response (IR) to TNF inhibitors (TNFi). Methods: Eligible pts in this 6-month, randomised, PBO-controlled, double-blind, multicentre, Phase 3 study had ≥6 months' PsA diagnosis, met CASPAR criteria, had active arthritis (≥3 tender/painful and ≥3 swollen joints) at screening and baseline, active plaque psoriasis at screening and IR to ≥1 TNFi (discontinued due to inadequate efficacy or adverse event [AE]). Pts were randomised 2:2:1:1 to tofacitinib 5 mg twice daily (BID), tofacitinib 10 mg BID or PBO (advancing to tofacitinib 5 or 10 mg BID in a blinded manner at Month [M]3). Ongoing treatment with 1 conventional synthetic DMARD was required. Pts were followed through M6. Primary endpoints were ACR20 response rate and change (Δ) from baseline in Health Assessment Questionnaire-Disability Index (HAQ-DI) at M3. Results: Pts were 92.1% white, 55.3% female and mean age was 50.0 years. At baseline, mean swollen and tender/painful joint counts were 22.0 and 11.8 respectively; mean HAQ-DI score was 1.3; 69.8% of pts had LEI >0; 49.2% had Dactylitis Severity Score (DSS) >0. Most patients (62.7%) had ≥3% BSA affected by psoriasis, for whom median PASI score was 7.9. Discontinuation rate at M3 was 7.6%, and 87.6% completed M6. ACR20 response and ΔHAQ-DI significantly improved with both tofacitinib doses vs PBO at M3 (Fig 1 A, B) and were maintained to M6 (Fig 1 C, D). Tofacitinib 5 mg and 10 mg BID demonstrated superior ACR20 response vs PBO as early as Week 2 (26.7% [p≤0.05] and 28.8% [p≤0.05] vs 13.0%). Secondary endpoints at M3 for tofacitinib 5 mg and 10 mg respectively were: ACR50 response, 29.8% (p≤0.05), 28.0% (p≤0.05); ACR70 response, 16.8% (not significant [NS]), 14.4% (NS); ≥75% improvement of PASI in pts with baseline BSA ≥3% and PASI >0, 21.3% (NS), 43.2% (p<0.0001); ΔLEI and ΔDSS in pts with baseline score >0: ΔLEI, -1.3 (p≤0.05) and -1.3 (p≤0.05) (least squares mean [LSM]); ΔDSS, -5.2 (p≤0.05) and -5.4 (p≤0.05) (LSM). Effects were maintained to M6. Frequency of serious AEs and discontinuations due to AEs was low and similar across treatment groups (Fig 1 E). The most common AEs were upper respiratory tract infection (5.3–10.8%), nasopharyngitis (1.5–10.7%) and headache (4.5–9.1%). Conclusions: In this study restricted to PsA pts with TNFi-IR, both tofacitinib doses appeared efficacious on musculoskeletal endpoints for treatment of PsA. No new safety risks were identified vs previous studies in other indications. Acknowledgements: Previously presented at ACR 2016, to be presented at AAD 2017 and reproduced with permissions. This study was sponsored by Pfizer Inc. Editorial support was provided by AG McCluskey of CMC and was funded by Pfizer Inc. Disclosure of Interest: D. Gladman Grant/research support from: Amgen, AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Pfizer Inc, Novartis, UCB, Consultant for: Amgen, AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Pfizer Inc, Novartis, UCB, Speakers bureau: Amgen, AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Pfizer Inc, Novartis, UCB, W. F. Rigby Grant/research support from: Amgen, Pfizer Inc, Roche, Consultant for: Bristol-Meyers Squibb, Eli Lilly, Pfizer Inc, Roche, V. Azevedo Grant/research support from: Bristol-Myers Squibb, GSK, Pfizer Inc, UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Janssen, Merck Novartis, Pfizer Inc, Serono, F. Behrens Grant/research support from: Abbvie, Pfizer Inc, Roche, Chugai, Prophylix, Bioline, Novartis, Consultant for: Abbvie, Pfizer Inc, Roche, Chugai, UCB, BMS, Celgene, MSD, Novartis, Biotest, Janssen, Genzyme, Lilly, R. Blanco: None declared, A. Kaszuba Consultant for: Janssen, Eli Lilly, Novartis, E. Kudlacz Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Menon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Hendrikx Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Kanik Shareholder of: Pfizer Inc, Employee of: Pfizer Inc